Instrumental Activities of Daily Living by Subjective and Objective Measures: The Impact of Depression and Personality - Numbers, Katya; Jang, Sujin; Brodaty, Henry; Sachdev, Perminder S.; Draper, Brian; Reppermund, Simone (Frontiers in Aging Neuroscience, 2022)
Objective: Previous research shows that depression and personality are independently associated with self- and informant-reports of ability to perform instrumental activities of daily living (IADLs). However, less is known about the association between depression and personality and performance-based measures of IADLs. We aimed to determine how depression and personality predict self-and informant-reports of IADL compared to performance-based measures of IADLs in a sample of older adults with normal cognition (NC) and Mild Cognitive Impairment (MCI). Methods: Participants were 385 older adults with NC (n=235), or a diagnosis of MCI (n=150), aged between 76 - 99-years from the Sydney Memory and Ageing Study. Participants underwent comprehensive neuropsychological and clinical assessments to determine global cognition and clinical diagnoses. Personality traits were measured by the NEO Five-Factor Inventory (NEO-FFI) and depression by the Geriatric Depression Scale (GDS). Subjective IADLs were self- and informant-reported Bayer Activities of Daily Living (B-ADL) scales and objective IADL was the Sydney Test of Activities of Daily Living in Memory Disorders (STAM). Linear regressions examined the relationship between depression and personality and the three types of IADL measures, controlling for all covariates and global cognition. Results: Participant-reported IADL, although associated with global cognition, were more strongly associated with GDS and NEO-FFI scores (conscientiousness and neuroticism). Informant-reported IADL were strongly associated with both global cognition and participants’ GDS scores. STAM scores were not associated with participants’ GDS or NEO-FFI scores; instead, they were predicted by demographics and global cognition. Conclusion: These results suggest that performance-based measures of IADL may provide more objective and reliable insight into an individual’s underlying functional ability and are less impacted by the participants’ mood and personality compared to subjectively reported IADL. We argue that performance-based IADL measures are preferable when trying to accurately assess everyday functional ability and its relationship to cognitive status. Where performance-based measures are not available (e.g., in some clinical settings), informant ratings should be sought as they are less influenced by the participant’s personality and mood compared to self-reports.